FORENSIC ACCOUNTING AND ITS FRAUD PREVENTION FUNCTION AND ITS EFFECTS ON THE MANAGEMENT OF INDUSTRIAL COMPANIES LISTED ON THE LIMA STOCK EXCHANGE - Merino Hurtado, Guillermo (2024)
The present research work called Forensic accounting and its fraud prevention function and its effects on the management of industrial companies listed on the Lima Stock Exchange, in which fraud prevention is identified as one of the main problems within the management of the company resulting in a potential loss of money, prestige, among others; This part of accounting control is not yet well defined, its concepts, functions and objectives, which is why our work contributes to the knowledge of this subject.The objective of this research is to demonstrate that occupational fraud can be prevented in real time through a Methodical and structured control system led by the accounting department, and this in turn by the forensic accountant as long as he has the skills, tools, and sufficient disciplines to be able to assume said preventive function.The focus of the research is on the various measurements related to the elements of vulnerability of the management of the company in which there is a series of operations that may result in a high risk of committing an occupational crime, therefore It should be within the company that the accounting professional should have the main function of controlling and protecting the company’s assets, through disciplines which are not traditional but are essential in current times. These tools are data mining, data management, big data, risk mapping, the use of red flags, criminology, criminology and documentology, etc.The methodology used for the research meets the conditions to be called applied since the scope of the research occurs in factual and exploratory reality since it allows us to identify the object of study, non-experimental observational, quantitative and qualitative correlational, as well through surveys carried out with accountants of industrial companies of companies listed on the Lima stock exchange as well as structured interviews with experts on the subject.In conclusion and after having carried out the corresponding comparisons; The proposed hypothesis was demonstrated, thus we have that effectively the forensic accountant can and must carry out quantitative and qualitative measurements and report in the shortest possible time to management on the risks of fraud, likewise the accounting professional must be prepared to be able to assume new forms of supervision. KEYWORDS: Forensic accounting, fraud prevention, business management, prevention, control, criminology, accounting functions, industrial companies.